Komodifikasi Agama: Studi Analisis terhadap Tampilan Agama di Media Televisi - Wibowo, Ari (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
The appearance of religion in television media tends to be colored by the principles of commercialization and capitalism. The religious program is presented not only has an impact on the exchange of values ​​(change values) but also on the exchange of money (change money). With a descriptive qualitative approach, this article seeks to explain the appearance of religion in several religious programs broadcast by several Indonesian television media. The observation method was used to identify several religious programs and controversial dramas, such as the drama "Bubur Naik Pilgrimage" on RCTI, Haji Medit drama on SCTV, and drama "Azab" on Indosiar. The result is that religious programs and dramas where shown on television are commercialized to attract the attention of the audience and increase ratings. So this is what led to the commodification of religion in several television media in Indonesia. The commodification of religion in Indonesian television media appeared during the month of Ramadan. Tampilan agama di media televisi cenderung diwarnai dengan prinsip komersialisasi dan kapitalis. Program acara relegi yang disajikan tidak hanya berdampak pada pertukaran nilai (change values) tetapi juga pada pertukaran uang (change money). Dengan pendekatan kualitatif deskriptif, artikel ini berupaya menjelaskan dan memaparkan tampilan agama dalam beberapa program religi yang siarkan oleh beberapa media televisi indonesia. Metode observasi digunakan untuk mengidentifikasi beberapa program religi dan sinetron yang kontroversial, seperti sinetron “Tukang Bubur Naik Haji” di RCTI, sinetron Haji Medit di SCTV, dan sinetron “Azab” di Indosiar. Hasilnya bahwa program acara religi dan sinetron yang ditampilkan di televisi dikomersialisasi untuk menarik perhatian khalayak dan meningkatkan rating. Sehingga inilah yang menyebabkan terjadinya komodifikasi agama di beberapa media televisi di Indonesia. Komodifikasi agama di media televisi Indonesia nampak pada saat bulan Ramadan.